Bone grafts: Characteristics, properties, indications, contraindications for predictable bone regeneration - Part 1. - Molano, Pablo Emilio; Soto Franco, Jorge Enrique (Revista Estomatología, 2025)
Objective: To perform a systematic literature search to summarize the characteristics, indications and contraindications as well as the requirements to obtain a predictable bone regeneration. Materials and methods: A systematic search was carried out in databases such as GOOGLE SCHOLAR, LILACs, PUBMED between 2002 and 2024. In addition, a manual search was performed according to the authors’ criteria. The articles that met the inclusion and exclusion criteria related to the objective of the present review were selected. Results: The systematic search yielded 350 articles of which 42 were included in the present review. Bone graft concepts, indications and contraindications as well as clinical requirements for predictable guided bone regeneration were extracted. Conclusion: Autografts remain the gold standard in terms of regeneration of neoformed bone tissue. Allografts and xenografts have also shown predictable results overcoming the limitation of autografts in terms of availability and lower morbidity.